Futures for the Wheatbelt - Is 2030 already here? - McKenzie, Fiona Haslam; Stehlik, Daniela (CSIRO Publishing, 2005)
The Western Australian Wheatbelt has experienced significant social, economic and environmental changes over the last 25 years which have impacted on the viability of the broadacre farm businesses which dominate the Wheatbelt economy as well as the efficacy of the communities that have supported the agricultural industry. This paper considers the consequences of these changes and how the agricultural industry and the people living in the Wheatbelt region have responded to the challenges. As well, the future of the region is considered, based on potential market and capacity building alternatives. It is contended that many of the social, economic and environmental indicators of the future have been in place for some time and that industry diversification and social options are already being trialled. It would appear that industry and individual resilience and creativity are key for the Wheatbelt?s survival in the future.